ANALISIS KADAR BOD DAN COD PADA AIR TAMBAK DI DESA X BEKASI: ANALISIS KADAR BOD DAN COD PADA AIR TAMBAK DI DESA X BEKASI - Jumriah Nur; Ladyka Viola Aulia Armawan (Klinikal Sains : Jurnal Analis Kesehatan, 2022)
Pond waters are one of the lands that can be used to improve the economic sector. The decline in pond water quality is caused by many factors including water sources, weather influences, treatment errors in the use of several treatments such as feed, fertilizer and so on. Pollutants in pond waters can affect the quality of the organisms that are kept in them, among others, can cause physiological and anatomical disturbances, thereby reducing protein levels in fish and shrimp muscles. One of the steps to determine the quality of pond water is feasible or not is to conduct a waste quality analysis using chemical indicators including BOD and COD. This type of research uses laboratory observation. Sampling was carried out at 3 stations on pond water in Village X Bekasi, using the Judgment or purposive Sampling method. The results showed that the BOD and COD values ​​in pond water in Village X Bekasi had exceeded the water threshold based on the class III water quality standard (PPRI No. 82/2001), for the BOD level the average value was 711 mg/L and the COD value averaged. an average of 10,150 mg/L.